Hybrid algorithms for service, computing and manufacturing systems : routing and scheduling solutions - Montoya-Torres, Jairo R., 1977- (Information Science Reference, 2012)
"This book explores research developments and applications from an interdisciplinary perspective that combines approaches from operations research, computer science, artificial intelligence, and applied computational mathematics"--Provided by publisher